2021
DOI: 10.1080/02665433.2021.1885479
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Australian Government’s Growth Centres programme 1972–1975

Abstract: From 1973 to 1975 a new Australian Government led by Gough Whitlam actively pursued plans to develop regional and sub-metropolitan Growth Centres with significantly boosted populations following a national strategy published in June 1973 which mapped a national coverage of prospective locations. The intention was for these centres to alleviate pressure on the capital cities considered overcrowded and deteriorating in efficiency and quality of life. The controversial dismissal of the Whitlam Government in 1975 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The quick rise and demise of DURD, in particular, seems to have only consolidated an Australian urban policy resolve to adhere to metropolitan primacy and the 'path dependency' critiqued by Troy (1999: 165). Bolleter et al (2021bBolleter et al ( : 1020 concluded that had DURD been able to operate in ways less centralist in its modus operandi, more nimble in its responses to counter urbanization trends, and with Federal Government funding sustained and private sector investment more skilfully leveragedthe gap between planned and achieved Growth Centre populations may have been closed even more … [R]edistribution of the national urban population could have been made more secure.…”
Section: Decentralisation and New Townsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quick rise and demise of DURD, in particular, seems to have only consolidated an Australian urban policy resolve to adhere to metropolitan primacy and the 'path dependency' critiqued by Troy (1999: 165). Bolleter et al (2021bBolleter et al ( : 1020 concluded that had DURD been able to operate in ways less centralist in its modus operandi, more nimble in its responses to counter urbanization trends, and with Federal Government funding sustained and private sector investment more skilfully leveragedthe gap between planned and achieved Growth Centre populations may have been closed even more … [R]edistribution of the national urban population could have been made more secure.…”
Section: Decentralisation and New Townsmentioning
confidence: 99%
“…Queensland's Gold Coast saw far and away the greatest increase (Wade 2004), offering, as Andrew Leach (2018: 142) has pointed out, 'an infrastructure based on … the paradoxical stance of offering an urbanised experience of "getting away from" the city'. A reappraisal of DURD growth centres found several had come close to their anticipated populations but had been eclipsed by the sheer scale of growth in larger urban conglomerations (Bolleter et al 2021b).…”
Section: The Turn Of the Centurymentioning
confidence: 99%